Health insurance eligibility and child health in Peru : an analysis of the "Seguro Materno-Infantil" program - Poggio Monteverde, María Virginia (2011)
Fil: Poggio Monteverde, María Virginia. Universidad de San Andrés. Departamento de Economía; Argentina.